IJTIHÃD MUHAMMADIYAH DALAM MENENTUKAN KE-HUJJAH-AN HADIS BIDANG AQIDAH DAN IBADAH - Kasman, Kasman (LP2M IAIN Mataram, 2011)
The research analyzes ijtihÃ¢d (legal reasoning) ofMuhammadiyah in determining the hujjiyat al-hadÃ®ts (the prophetictradition as authoritative source) in the Majelis Tarjih Decisionsfrom 1929 to 1972, pertaining to âaqÃ®dah (theology) and âibÃ¢dah(worship). Building on inter-textual analysis, TakhrÃ®j (verification)al-hadÃ®ts and coherence analysis, the study finds three importantthings: First, Muhammadiyah employed two different strategiesin holding the hadis as authoritative source; regarding theology, ituses khabar mutawatir, and al-sunnah al-shahÃ®hah concerningworship. It emphasizes on continuation of transmission and criteriaof transmitters as âadl (just) and dlabit (entrusted), but less on thecritics of matn (substance) of tradition. Second, there are somedifferences of matn al-hadÃ®ts in the collection used by TarjihDecisions. In Kitab Iman, 6 traditions are classified as Ã¢hÃ¢d(transmitted only through one companion), but none of them isdlaâÃ®f (weak). Meanwhile, regarding the issue of worship, thereare 2 weak traditions. Third, theoretically, the Muhammadiyahlegal reasoning produces sound legal rules despite the fact thatthese are too general to use and thus less useful in some respects.The Muhammadiyah ijtihÃ¢d in the field of hadÃ®ts can be classifiedinto tarjÃ®hÃ® (selection), or even taqlÃ®dÃ® (blind acceptance). This leadinto inconsistency as it was seen in the use of weak traditionsregarding the issues of worship and tradition transmitted through